The concept of the method of charged particle beam density distribution measurement based on mathematical reconstruction; Russian Particle Accelerators Conference (RuPAC-23) - Grigorieva (Grigorjeva) A. A. Anna Anatoljevna; Bulavskaya A. A. Angelina Aleksandrovna; Miloichikova I. A. Irina Alekseevna; Stuchebrov S. G. Sergey Gennadevich; Bushmina E. A. Elizaveta Alekseevna (2023, 2023)
Title screen